Challenges and Opportunities in University-Based Humanitarian Mapathons: Enhancing Citizen Science Contributions to Open Spatial Data - J. Trojan; T. Srnečková (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Citizen science has become a key paradigm for the creation and improvement of digital geographic data, especially in areas often neglected by commercial mapping initiatives (Vohland et al., 2021). University mapathons are an important tool for engaging students in humanitarian mapping and have the potential to contribute significantly to the quality and quantity of volunteered geographic data as a gathering place for a particular community interested in self-development and contributing to society-wide development. This paper analyses the complex aspects related to the organisation and implementation of mapathons in a university setting, focusing on a case study of Tomas Bata University in Zlín.